(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2026)
This study delves into the efficacy of the Learning-by-Doing approach in bolstering the speaking abilities of second-grade students at SMAN 3 Soppeng, alongside exploring teachers’ perceptions of this method. Conducted as a qualitative investigation, it employs observation and interviews within a cluster sample of 32 students across three classes to assess the impact of practical learning experiences. Despite facing challenges such as time constraints and occasional concept misinterpretations, the method, supported by a conducive learning environment and involving group practices, emphasizes active student engagement, a student-centered approach, teacher facilitation, and an integrated curriculum to enhance creativity and teamwork. The findings indicate positive outcomes, including improved speaking skills and high student enthusiasm, thereby underscoring the effectiveness and potential of the Learning-by-Doing approach in educational settings.